Enhanced full solar spectrum photocatalysis by nitrogen-doped graphene quantum dots decorated BiO2-x nanosheets: Ultrafast charge transfer and molecular oxygen activation - Chen, Fei; Liu, Lian-Lian; Zhang, Ying-Jie; Wu, Jing-Hang; Huang, Gui-Xiang; Yang, Qi; Chen, Jie-Jie; Yu, Han-Qing (Applied catalysis. B, Environmental, 2020)
[Display omitted] •N-GQDs/BiO2-x nanoscale heterojunctions were prepared based on 0D/2D interface engineering.•Tetracycline was efficiently degraded under full-spectrum, visible and NIR light irradiations.•Highly oxidative capacity of holes and reductive properties of electrons were achieved.•Synergistic effects were found to accelerate the molecular oxygen activation. It is still challenging to produce superoxide and hydroxyl radicals through activating molecular oxygen under broad-spectrum light in environmental photocatalysis. In this work, nitrogen-doped graphene quantum dots (N-GQDs) modified BiO2-x nanosheets were successfully fabricated and exhibited superior performance in light-harvesting, electron-hole pair separation, and full-spectrum driven molecular oxygen activation. The hybridized photocatalyst with a N-GQDs weight ratio of 0.4wt% (GBO-0.4) exhibited an excellent photocatalytic activity toward tetracycline degradation with a 4.0-fold, 2.9-fold and 5.5-fold higher reaction rate under full-spectrum, visible and near-infrared light irradiations than that of pure BiO2-x, respectively. The enhanced photocatalytic performance was ascribed to the electron collection effect and up-conversion photoluminescence properties of the N-GQDs as well as the synergistic effects of the developed nanojunction. Efficient molecular oxygen activation was achieved via the construction of a bulk-to-surface channel between BiO2-x and N-GQDs. DFT calculations were also used to explore the geometric and electronic structure variations of BiO2-x after the introduction of N-GQDs. The high photostability and mineralization ability toward tetracycline degradation confirm the promising application prospects of the N-GQDs/BiO2-x photocatalyst. This work provides a rational strategy for designing 0D/2D nanoscale heterostructure photocatalysts with improved full-spectrum photoactivity for environmental applications.